A Semantic Framework to Support the Management of Cloud-Based Service Provision Within a Global Public Inclusive Infrastructure. Issue 1 (2nd January 2016) - Giakoumis, Dimitris; Mavridou, Efthimia; Votis, Konstantinos; Giannoutakis, Konstantinos; Tzovaras, Dimitrios; Hassapis, George
ABSTRACT: Cloud computing has opened a new era in e-commerce. As the growth and complexity of public and private clouds increases, novel solutions are needed, enabling vendors to effectively manage the cloud-based distribution of their services. To this end, this paper presents a novel semantic framework with the main aim to support providers in the overall cloud-based service provision process, in terms of service ownership, licensing, and usage monitoring. The base of our framework is an ontological schema that models service business rules definition and license agreements registration, as well as service usage monitoring, with a special focus on web service and software applications cloud-based distribution. Our proposed ontology supports complex distribution schemas, related to multiple vendor-based service distribution, as well as personalized discount schemas, facilitating the deployment of marketing strategies during cloud-based service provision. On top of this ontological schema, we have further developed service and provider reputation and trust inference mechanisms, which operate on the basis of both service usage statistics and subjective end user feedback. Taking a step forward from the state of the art, our mechanisms also provide personalized discount suggestions, further facilitating providers in defining marketing strategies. Apart from supporting providers, our mechanisms also facilitate users in service and provider selection. In order to examine the application of our framework in practice, we have developed a user interface that provides basic features of our framework, within the context of a real cloud, oriented toward personalized cloud service provision; our framework has been integrated in the "Cloud4All" Global Public Inclusive Infrastructure (GPII).